The Adaptation of Islamic Religious Education Learning Model of the Independent Curriculum - Danial, Muhammad; Widodo, Hendro (Universitas Islam Negeri Raden Intan Lampung, 2022)
Indonesian curriculum transformation into an independent curriculum necessitates the readiness of schools and all of their components to adapt to these changes. As a result, every school's Islamic religious education learning process is required to conduct learning by following the independent curriculum. This study employs the qualitative method with a descriptive design. The data is gathered through observation and interviews with informants. The study’s respondents were school principals, vice principals of the curriculum section, Islamic Religion education teachers, and student representatives from SMA Negeri 5 Tana Toraja. The data found in this study was analyzed by collecting data in process and data in the field. According to the findings, Islamic religious education is taught at SMA Negeri 5 Tana Toraja in the framework of implementing differentiated learning in the independent curriculum. The adoption of the independent curriculum in learning Islamic Religious Education at SMA Negeri 5 Tana Toraja lays a greater emphasis on teacher readiness in carrying out differentiated learning. Adopting the Independent Curriculum in learning Islamic Religious Education in schools necessitates facilities, space, and many policies to increase teachers' knowledge and creative power.